Structural-Semantic Patters with Suffixes Expressing Resemblance in Modern English and Modern Armenian - Karapetyan, Lili; Yakhnyan, Armine (Armenian Folia Anglistika, 2009)
The study focuses on the formation of derivative adjectives containing suffixes that express resemblance in Modern English and Armenian on the synchronic level. The peculiarities of the interaction of the constituents of those patterns (roots and affixes) are studied both from semantic and structural points of view, revealing some similarities and differences of word-building systems in both languages, which will go a long way in working out the typology of patterns.